Hierarchical self-assembly of block copolymers for lithography-free nanopatterning - Kim, Bong Hoon; Shin, Dong Ok; Jeong, Seong-Jun; Koo, Chong Min; Jeon, Sang Chul; Hwang, Wook Jung; Lee, Sumi; Lee, Moon Gyu; Kim, Sang Ouk (WILEY-V C H VERLAG GMBH, 2008)
Hierarchical self-assembly of block copolymers has been achieved by two steps of sequential ordering processes, consisting of self-organized micropatterning from a dewetting block polymer solution and thermal annealing. The self-organized micropattern induces the spontaneous alignment of self-assembled lamellae (see figure), which is successfully applied for a lithography-free, ultra-large-scale nanopatterning.
Keywords: SINGLE-LAYER FILMS; THIN-FILMS; PATTERNS; ARRAYS; SOLIDIFICATION; NANOSTRUCTURE; ORIENTATION; CYLINDERS; SURFACES